Experimental schistosomiasis in primates in Tanzania: Preliminary observations on the susceptibility of the baboon Papio anubis to Schistosoma haematobium and Schistosoma mansoni - Jordan, P. (1967)
Laboratory infection of animals with Schistosoma haematobium is generally unsatisfactory as adult worms invariably inhabit the portal venous system rather than the vesical plexus as in man. However, it was thought that certain primates might prove more valuable for experimental studies of schistosomiasis than the usual laboratory animals. Baboons, Papio anubis, were therefore exposed to cercariae of S. haematobium and the pattern of egg excretion in stools and urine was followed quantitatively. Histological studies of various organs were made and it was found that although eggs were excreted in the faeces, they were also passed in the urine and that tissue changes in the bladder were similar to those found in human infections. It is suggested that the sequelae of S. haematobium infection found in man might develop in baboons and that the animal may be useful for studying their development in the laboratory.